2020
DOI: 10.2147/idr.s261579
|View full text |Cite
|
Sign up to set email alerts
|

<p>NDM-1 Carbapenemase-Producing Enterobacteriaceae are Highly Susceptible to Ceragenins CSA-13, CSA-44, and CSA-131</p>

Abstract: Background and Purpose: Treatment of infections caused by NDM-1 carbapenemaseproducing Enterobacteriaceae (CPE) represents one of the major challenges of modern medicine. In order to address this issue, we tested ceragenins (CSAs-cationic steroid antimicrobials) as promising agents to eradicate various NDM-1-producing Gram-negative enteric rods. Materials and Methods: Susceptibility to CSA-13, CSA-44, and CSA-131 of four reference NDM-1 carbapenemase-producing strains, ie, Escherichia coli BAA-2471, Enterobact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 41 publications
5
24
0
Order By: Relevance
“…Moreover, considerable changes of mechanical properties of the tested bacteria were noted accompanied by a decrease of cellular stiffness and adhesion force. Overall, all of these results obtained on the nano-level extend our knowledge on the utility of ceragenins in the treatment of drug-resistant bacterial pathogens [71].…”
Section: Bacteriasupporting
confidence: 72%
See 1 more Smart Citation
“…Moreover, considerable changes of mechanical properties of the tested bacteria were noted accompanied by a decrease of cellular stiffness and adhesion force. Overall, all of these results obtained on the nano-level extend our knowledge on the utility of ceragenins in the treatment of drug-resistant bacterial pathogens [71].…”
Section: Bacteriasupporting
confidence: 72%
“…Likewise, in our research ( Figure 3 ), we used AFM to assess the bactericidal effects of ceragenins (CSA), i.e., synthetic, lipid-based analogs of natural antimicrobial peptides, against NDM-1 carbapenemase-producing K. pneumoniae [ 71 ]. In a compelling number of studies, ceragenins were demonstrated as potent antimicrobial agents with a membrane-permeabilizing mechanism of action [ 2 , 5 , 72 ].…”
Section: Afm-based Investigation As a Novel Approach To Fight Withmentioning
confidence: 99%
“…On the other hand, to address the possible toxicity of CSAs used alone, our previous data underlined that CSA-131 at concentrations ranging from 1–10 µg/mL caused no significant hemolysis, even after 12 h of incubation [ 35 ]. Moreover, the recent data also demonstrated that MNP-CSA-13 at concentrations of 1–100 µg/mL had no effect on the hemoglobin released from RBC [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the remaining members belong to the second generation of CSAs [ 34 ]. A variety of studies confirmed that the second-generation of CSAs, notably CSA-131, possess potent antimicrobial activity against a broad spectrum of microorganisms such as carbapenem-resistant E. coli, K. pneumoniae, E. cloacae [ 35 ], or P. aeruginosa [ 36 ]; colistin-resistant K. pneumoniae and Acinetobacter baumannii [ 37 , 38 ]; as well as uropathogenic E. coli strains [ 39 ]. Moreover, Hacioglu et al have demonstrated the antibiofilm activity of CSA-131 against C. albicans cells in both mono- and multispecies biofilms, i.e., comprising of C. albicans and MRSA or MSSA (methicillin-susceptible S. aureus ) strains [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation